Analisa Kognitif Model Blended Learning Dengan Pendekatan Kalkulus Dasar - Sumihar Simangunsong; Ika Trisna (Department of Physics Education, Universitas Mataram, 2021)
This research was motivated by the low learning outcomes of students in basic physics courses. This is due to the learning of basic physics which requires mathematical analysis in interpreting and analyzing the variables of physical quantities. The purpose of this study was to see the increase in learning outcomes as a result of the application of the blended learning model with the basic calculus approach. This approach is used because basic calculus can analyze basic physical substances through differential and integral languages. The sample of this research was students majoring in mining ISTP Medan. The research method used was a Quasi-experimental one group design. To see the learning outcomes, a learning outcome test is used and a gain test is used to improve learning outcomes. The results showed that the gain test at the first meeting was 0.6, the second meeting was 0.6 and the third meeting was 0.7 with the high category. From research result there is an increase in the gain for each meeting, it is concluded that there is an increase in student learning outcomes as a result of the blended learning model with the basic calculus approach.